Pengembangan Kelurahan Penaraga Sebagai Produsen Sepeda Listrik (Fi Bike Elektric) Di Kota Bima - Lubis Hermanto; Ariani Rosadi; Mas’ud Mas’ud; Syamsuddin Syamsuddin; Jasman Jasman (LPPM Universitas Dharma Andalas, 2023)
The rapid development of the business world and the industrial world has had a very diverse impact on people's lives. The business world and the industrial world which are increasingly diverse are able to influence people's mindsets to change. Various forms of change in society, whether in the social, economic, political, and cultural sectors, have resulted in the emergence of new ideas and innovations, especially in the field of transportation technology. Transportation technology is demanded to be more innovative considering the dwindling natural resources, especially fuel oil (BBM). The innovators tried various ways to be able to create environmentally friendly transportation, one of which was an electric bicycle (electric bicycle). The methods used include various lectures, demonstrations, and exercises. The results of this development will be beneficial for youth and the community, the learning and teaching process in development activities will be more interesting with the use of more varied learning media. In addition, the existence of development activities through electric bicycle innovation (fi-bike elektric) will increase the skills of youth and the community in developing creativity so that it will support and create superior youth and society so that they are able to create ideas and innovations in the era of global competition as it is today, especially in alternative transportation.